SISTEM INFORMASI PEMASARAN DAN PENJUALAN SABLON BERBASIS WEBSITE PADA ASG_PRINT - Aryobenno Putra Chaniago, (2022)
ASG_print's screen printing business is a business that is engaged in screen printing, currently the process carried out at ASG_print can still be considered manual in the ordering process, marketing, recording transactions, and communicating with consumers. This is a problem because consumers have to come directly to place an order, manual records may be lost, and the absence of online marketing causes a lack of people who know ASG_print. To overcome these problems, the research will create a marketing and sales information system that can help the ASG_print screen printing business in overcoming the problem. This system is built based on a website using PHP and a MySQL database, where consumers can place orders online, view products and product details. This system can also help the marketing process of ASG_print's screen printing widely online. In overcoming this, the authors built a system using the waterfall method and UML modeling which was built using a Laravel framework and MySQL database. So the results of this study are to build a website-based sales and marketing information system that can help screen printing companies to expand their sales network, make it easier for buyers and store sales transaction data in ASG_print.